Yeterince Keratinize Olmayan Mukoza Periimplantit İçin Bir Risk Faktörü mü? Literatür Taraması - Adnan Tezel; Sevilay Yeğinoğlu; Özge Tezel (Atatürk University, 2024)
Is Insufficiently Keratinized Mucosa a Risk Factor for Periimplantitis? A Literature Review ABSTRACT In this study, a literature review was conducted including human studies assessing keratinized presence and extent in PubMed and Scopus whether insufficiently keratinized mucosa s risk factor for periimplantitis or not. The end of this review, we concluded that . The KM is important for masticatory stresses in the tooth margin or crown, and results in esthetics that are more favorable, overall comfort, and simplified brushing. Therefore, the presence of KM in the surrounding dental implant (DI) space is important for the prevention of inflammation, plaque buildup, gingival recession, and occurring periimplantitis. Keywords : Keratinized mucosa, Periimplantitis, Dental implants ÖZ Bu çalışmada, PubMed ve Scopus'ta keratinize varlığı ve yaygınlığını değerlendiren, yetersiz keratinize mukozanın periimplantitis için risk faktörü olup olmadığını değerlendiren insan çalışmalarını içeren bir literatür taraması yapılmıştır. Bu incelemenin sonunda şu sonuca vardık. KM, diş kenarındaki veya krondaki çiğneme stresleri için önemlidir ve daha olumlu estetik, genel konfor ve daha basit fırçalamayla sonuçlanır. Bu nedenle, çevredeki diş implantı (DI) boşluğunda KM'nin varlığı, iltihaplanmanın, plak oluşumunun, diş eti çekilmesinin ve ortaya çıkan periimplantitin önlenmesi için önemlidir.. Anahtar Kelimeler: Keratinize mukoza, Periimplantitis, Diş implantları